2017
DOI: 10.1016/j.radonc.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of failure in limited-stage small cell lung cancer: Implications of TNM stage for prophylactic cranial irradiation

Abstract: Background and Purpose The relationship between tumor-node-metastasis (TNM) stage and patterns of failure in limited-stage small cell lung cancer (LS-SCLC) remains unclear. We hypothesized that TNM stage predicts brain metastasis risk, and could inform the use of prophylactic cranial irradiation. Material and Methods We reviewed 283 patients with stage I–IIIB SCLC. Competing-risks regression was used to analyze local, distant, and brain failure. Multivariate analysis was used to evaluate the effect of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…A total of 6 studies reported the BM incidence in those populations. Wu, A. J.et al recently reported that the 5-year cumulative incidence of brain metastasis for stage I/II and III were 12% and 26% in a review of 283 patients, which was not included in our analysis, since the BM rates of I and II stage patients were combined together 31 . After combining all the results, a low metachronous BM incidence (0.12, 95% CI: 0.08-0.17) was observed, with no heterogeneity (I 2 = 0.0%, P-heterogeneity=0.79) (Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 6 studies reported the BM incidence in those populations. Wu, A. J.et al recently reported that the 5-year cumulative incidence of brain metastasis for stage I/II and III were 12% and 26% in a review of 283 patients, which was not included in our analysis, since the BM rates of I and II stage patients were combined together 31 . After combining all the results, a low metachronous BM incidence (0.12, 95% CI: 0.08-0.17) was observed, with no heterogeneity (I 2 = 0.0%, P-heterogeneity=0.79) (Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study by Farooqi et al identified primary tumors ≥5 cm to be the only independent risk factor (HR 1.66) for development of brain metastases (7). Wu et al defined LS-SCLC as T3N3M0 disease or lower and found that stage III disease was predictive of brain metastases when compared with stage I/II disease (HR 2.09) (8). These two studies indicate that in LS-SCLC, where PCI is currently standard of care, individualized discussion of whether to deliver PCI for stage I and II patients should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown an association between the size of primary tumor and overall extent of disease with an increased rate of brain metastases in patients with LS-SCLC (7,8). For patients with ES-SCLC, it has been reported that patients with less than 5 kg weight loss and good response to chemotherapy were at a higher risk for developing brain metastases (9).…”
Section: Original Articlementioning
confidence: 99%
“…With the advancement of SCLC research, the TNM staging system emerged and has gradually become more widely used. Abraham et al [19] found that TNM staging was more accurate in predicting distant metastasis, brain metastasis, and survival in limited-stage SCLC patients. Zhu et al [20] reported that the 3-year incidence of brain metastasis in TNM stage I patients was 9.7%, which was signi cantly lower than that in TNM stage II (18.5%) and stage III patients (35.4%), and they suggested that TNM stage I patients did not need preventive cranial radiation treatment.…”
Section: Survival Analysismentioning
confidence: 99%